HORTICULTURAL CROPS VALUE ADDITION FOR NUTRITIONAL SECURITY - Kulshrestha , Kalpana (International Journal of Research -GRANTHAALAYAH, 2018)
Nutritional well-being is a sustainable force for health and development of people and maximization of human genetic potential. From the beginning of human history, food has been considered as the major factor in maintaining well-being and health of individuals. Active ingredients in food which are effective in promoting human health include amino acids, fats dietary fiber, antioxidants, pigments, vitamins and minerals which are present in different food groups such as pulses, cereals, legumes, oilseeds, fruits and vegetables. Among all these food groups, fruits and vegetables play a significant role in human nutrition, especially as a source of vitamins, minerals and dietary fiber. The different fruits and vegetables like carrots, tomatoes potatoes, ginger, green leafy vegetables and the like are important protective foods because of their nutritional value and antioxidant properties. Value addition of such fruits and vegetables by formulation of different value-added products are an important source of nutritional security.